Analysis of Differences in Legal Protection Towards Consumers in Business Transactions Based on Different Types of Contracts - Ningsih, Familla Dwi; Dewi, Ery Arsita; Mawahib, Mawahib; Prabowo, Muhammad Shidqon; Kustanto, Anto (LifeSciFi, 2024)
This research aims to analyze differences in legal protection for consumers based on the type of contract in business transactions. Primary data was obtained through unstructured interviews with 385 respondents, and secondary data was collected from various related sources. Data analysis was carried out using the ANOVA test to evaluate the average difference in legal protection between sales, rental, and service contracts. Analysis results ANOVA shows a significant difference in legal protection for consumers based on contract type. Is known that sales and purchase contracts provide significantly higher legal protection compared to rental and service contracts. These findings indicate that the type of contract has a significant impact on the level of legal protection received by consumers. The implication of this research is the need for special attention to regulations and legal protection standards in rental and service contracts to ensure fairness for consumers.